Dynamics of the Epidemic Process of Tick-Borne Encephalitis in Irkutsk Region in 2001–2021 - M. I. Tolmacheva; A. Ya. Nikitin; E. I. Andaev; I. G. Chumachenko (Проблемы особо опасных инфекций, 2023)
The aim of this work was to analyze the spatial and temporal features of the epidemic process dynamics of tick-borne encephalitis (TBE) in Irkutsk Region in 2001–2021.Materials and methods. The data of the Rospotrebnadzor Administration for the Irkutsk Region, the Reference Center of the Irkutsk Research Anti-Plague Institute, the materials of the state statistical reporting form No. 2 “Information on infectious and parasitic diseases”, and scientific publications were analyzed. The chronological and chorological features of the change in the incidence of TVE have been traced. In the latter case, the administrative-territorial formations (ATF) of the subject were differentiated by epidemiological risk groups over two ten-year periods: 2001–2010 and 2011–2020. At each time interval, the grouping of areas according to the level of TBE incidence was carried out using the calculation of 95% confidence interval. Time sequences of observations were analyzed using the construction of regression equations. Standard methods of variation statistics in the Microsoft Excel were deployed.Results and discussion. Over the course of the 21st century, the incidence of TBE in Irkutsk Region has been declining. Based on 2001–2010 data, there were no cases of TBE in six ATF, and endemic areas were divided into three groups: with low (15 districts), medium (6) and high (8) incidence of TBE. A separate assessment of morbidity rates was conducted in the administrative center of the entity, the city of Irkutsk. In 2011–2020, the structure of ATF with varying epidemiological risk of TBE underwent a change. Six non-endemic areas, groups of low (12 ATFs), medium (9), high (6) and very high (2) epidemiological risk were identified. The spatial arrangement of high epidemiological risk zones changed, and their area increased. Each ATF cluster with different TBE incidence in 2011–2020 is characterized by the number of TBE cases and the volume of measures to prevent the infection. It is concluded that preventive measures were insufficient in ATF groups of high and very high epidemiological risk.